Development and identification of three functional markers associated with starch content in lotus (Nelumbo nucifera) - Cheng, Teng; Zheng, Xingwen; Xie, Keqiang; Liu, Jiangdong; Zheng, Xingfei; Jin, Surong; Diao, Ying; Hu, Zhongli; Wang, Jianxiong (Scientific reports, 2020)
It have been significantly demonstrated that Hexokinase (HXK), Granule-bound starch synthase (GBSS) and ADP-glucose pyrophosphorylase (AGPase) are three critical enzymes in the starch biosynthetic pathway and are related to starch (amylose, amylopectin and total starch) content in lotus. It is important to develop functional markers in marker-assisted selection of lotus breeding. So far there have been few reports about lotus functional markers. In this study, based on insertion-deletions (INDELs) and single-nucleotide polymorphisms (SNPs), we developed three functional markers, FMHXK-E1, FMGBSS-I8 and FMAGPL-I1. FMHXK-E1 was developed based on polymorphisms of two haplotypes of NnHXK . 26 lotus cultivars that the 320-bp fragment presented in NnHXK had a lower content of amylose and a higher content of amylopectin. FMGBSS-I8 was developed based on polymorphisms of two haplotypes of NnGBSS . The group containing 32 lotus cultivars with the 210-bp fragment had less amylose content and more amylopectin content. FMAGPL-I1 was developed based on polymorphisms of two haplotypes of NnAGPL (ADP-glucose pyrophosphorylase large subunit gene). The group containing 40 lotus cultivars with the 362-bp fragment had less amylopectin, total starch content and more amylose content. According to the study, FMHXK-E1, FMGBSS-I8 and FMAGPL-I1 are closely related to lotus starch content. It could be provided research basis for molecular assisted selection of lotus starch content improve breeding efficiency.